Penetration of Silver Diamine Fluoride in Deep Carious Lesions of Human Permanent Teeth: An In Vitro Study - Jutharat Manuschai; Supitcha Talungchit; Supawadee Naorungroj (Hindawi Limited, 2021)
Background. When silver diamine fluoride (SDF) is used in conjunction with conservative caries removal in deep carious lesions, the distribution depth of silver is critical for safety and effectiveness. Objective. The purpose of this study is to determine the effect of selected caries removal on silver penetration when 38% SDF is applied to deep carious lesions in permanent teeth. Methods. Extracted permanent teeth with caries extending to the inner third of the dentin were used (N = 18). The periphery of the carious lesion was completely removed to the dentinoenamel junction (DEJ). In group A (n = 9), no further removal of carious tissue was performed, leaving necrotic dentin inner to the DEJ, whereas in group B (n = 9) superficial necrotic dentin was completely removed until leathery, slightly moist, reasonably soft dentin remained. SDF was applied for 3 minutes in both groups. Microcomputer tomography (micro-CT) and field emission scanning electron microscopy coupled with energy-dispersive X-ray spectroscopy (FESEM-EDS) were used to measure mineral density and silver distribution. The silver penetration depth/lesion depth (PD/LD) ratio was calculated for each sample. The Mann-Whitney U test was used to compare differences between the two groups. Results. The micro-CT analysis showed that the PD/LD ratios of group B (1.07-2.29) were marginally greater than those of group A (1.00-1.31). However, a statistically significant difference was not observed (pvalue = 0.5078). When stratified by remaining dentin thickness (RDT), the PD/LD ratios of group B were still greater than those of group A only when RDT was >500 µm. The FESEM-EDS analysis indicated that silver particles precipitated throughout the entire thickness of the carious lesions. Conclusion. Applying SDF on a deep carious lesion and leaving the necrotic dentin pulpally did not affect silver penetration. However, the extent to which silver penetrates the remaining dentin beneath the lesions is dependent on the amount and characteristics of that dentin.